Kehidupan Sosial Tiga Tokoh Korban Pembunuhan Berantai dalam Novel The ABC Murders karya Agatha Christie - Siti Nursuciati (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2021)
This research is entitled “Kehidupan Sosial Tiga Tokoh Korban Pembunuhan Berantai dalam Novel The ABC Murders karya Agatha Christie”. It aims at finding out the description of the social life background of the three serial murder victims in this novel. It is also aims at finding out the influence of the social life of the three characters on the serial murder case. The method used in this research is qualitative descriptive with sociological literature approach. This research used the theory of the characters by Abrams and Harpham (2009), character and plot relations theory by Nurgiyantoro (2015) and sociological dimension theory by Waluyo (in Wicaksono, 2017). The result found in this research is the description of the social life background from the three serial murder victims character they are occupation, family relations, age, nationality, wealth background, living condition, relations with the community, hobby or habits and social stratification. Then, the influence of the social life of the three characters on the serial murder case that contained in this novel is occupation aspects of Mrs. Alice Ascher and Elizabeth Barnard character, as well as family relations and welath background aspects of Sir Carmichael Clarke character.